On the word of a Jew: religion, reliability, and the dynamics of trust - Caputo, Nina; Hart, Mitchell Bryan (Indiana University Press, 2019)
"What, if anything, does religion have to do with reliability? When and how did religious difference matter when it came to trusting the word of another? In today's world, we take it for granted that being Jewish should not matter when it comes to acting or engaging in the public realm, but this was not always the case. The essays in this volume look at how and when Jews became reliable and trustworthy in the areas of jurisprudence, medicine, politics, academia, culture, business, and finance. As they explore issues of trust and mistrust, they reveal how the caricature of the Jew and Jews move through religious, political, and legal systems. While the volume is framed as an exploration of Jewish and Christian relations, it grapples with perceptions of Jews and Jewishness from the biblical period to today, from the Middle East to North America, and from Ashkenazi and Sephardi traditions. Taken together these essays reflect on a mechanics of trust, and sometimes mistrust, in everyday interactions involving Jews."--